Band alignment of Al2O3 with (−201) β-Ga2O3. (August 2017) - Carey, Patrick H.; Ren, F.; Hays, David C.; Gila, B.P.; Pearton, S.J.; Jang, Soohwan; Kuramata, Akito
Abstract: X-Ray Photoelectron Spectroscopy was used to determine the valence band offset at Al2 O3 /β-Ga2 O3 heterointerfaces. The Al2 O3 was deposited either by Atomic Layer Deposition (ALD) or rf magnetron sputtering and the synthesis method was found to have a very significant effect on the resulting band alignment. The bandgaps of the materials were determined by Reflection Electron Energy Loss Spectroscopy as 4.6 eV for Ga2 O3 and 6.9eV for Al2 O3 deposited by either method. The valence band offset was determined to be 0.07eV ± 0.20 eV (straddling gap, type I alignment) for ALD Al2 O3 on Ga2 O3 and -0.86 ± 0.25 eV (staggered gap, type II alignment) for sputtered Al2 O3 . This led to conduction band offsets of 2.23 ± 0.60 eV for ALD Al2 O3 and 3.16 ± 0.80 eV for sputtered Al2 O3, respectively. The choice of deposition method for the dielectric alters the type of band alignment for the Al2 O3 /Ga2 O3 system from type I alignment to type II. Since the main difference is expected to be the disorder at the dielectric/Ga2 O3 interface, this shows how synthesis method can affect the resulting band alignment. Highlights: We measured the band offsets of Al2 O3 on Ga2 O3 . Band alignment is nested (type I), with a valence band offset of 0.07 eV, for ALD Al2 O3 . For sputtered Al2 O3, the band alignment is type II, with a valence band offset of −0.86 eV.